Identification of conserved amino acid residues critical for human immunodeficiency virus type 1 integrase function in vitro. - Engelman, A (1992)
We have probed the structural organization of the human immunodeficiency virus type 1 integrase protein by limited proteolysis and the functional organization by site-directed mutagenesis of selected amino acid residues. A central region of the protein was relatively resistant to proteolysis. Proteins with altered amino acids in this region, or in the N-terminal part of the protein that includes a putative zinc-binding motif, were purified and assayed for 3' processing, DNA strand transfer, and disintegration activities in vitro. In general, these mutations had parallel effects on 3' processing and DNA strand transfer, suggesting that integrase may utilize a single active site for both reactions. The only proteins that were completely inactive in all three assays contained mutations at conserved amino acids in the central region, suggesting that this part of the protein may be involved in catalysis. In contrast, none of the mutations in the N-terminal region resulted in a protein that was inactive in all three assays, suggesting that this part of integrase may not be essential for catalysis. The disintegration reaction was particularly insensitive to these amino acid substitutions, indicating that some function that is important for 3' processing and DNA strand transfer may be dispensable for disintegration.